Aplicação de revestimentos à base de alginato de sódio incorporados de bactérias láticas para controle de antracnose em goiaba e manga - Fernandes, Karina Felix Dias (2021)
Anthracnose caused by fungi of the Colletotrichum spp. it is considered one of the main post harvest diseases that attack guava and mango, due to the severity of the developed symptoms, which cause significant economic losses. The method traditionally applied to control this infection is the use of chemical fungicides. However, the consumer market has been increasingly concerned about the long-term harmful damage caused by these substances, both to the environment and to human health. Thus, there is a demand for alternative technologies to control the causative agents of anthracnose in guava and mango. Among the emerging technologies, the application of biological control agents, such as lactic acid bacteria, has been considered an innovative biopreservation strategy, extending the shelf life of fresh and minimally processed fruits. The application of biocontrol agents, in combination with coating materials, increases the effectiveness in inhibiting the growth of phytopathogens. Sodium alginate is a polysaccharide commonly used to formulate edible coatings due to its film forming capacity, biodegradability, biocompatibility and low toxicity characteristics. This study aimed to develop and evaluate the application potential of coatings formulated based on sodium alginate and added with potentially probiotic lactic bacteria strains, as well as evaluating the effectiveness of coatings to reduce the development and severity of anthracnose caused by different pathogenic species of Colletotrichum (C. asianum, C. fructicola, C. tropicale, C. siamense, C. karstii, C. gloeosporioides) during 15 days of storage at room temperature (25±0.5 ºC) in guava cv. Paluma and sleeve cv. Palmer. The effects of the formulated coatings on some physicochemical parameters indicative of the general postharvest quality during storage were also evaluated. The eight strains of lactic acid bacteria tested caused strong inhibition of mycelial growth (29.2 - 100%) of all Colletotrichum target species in vitro. Among the eight tested lactic acid bacteria strains, Levilactobacillus brevis 59, Lactiplatibacillus pentosus 129, Limosilactobacillus fermentum 263 showed the greatest inhibitory effects on the different strains of Colletotrichum tested, being selected for incorporation in sodium alginate coatings. These lactic acid bacteria strains showed viable cell counts greater than 6 log CFU/mL in the sodium alginate coatings during 15 days of storage at room temperature. The application of coatings formulated with sodium alginate and L. brevis 59, L. pentosus 129 or L. fermentum 263 delayed the development and decreased the severity of anthracnose lesions in guavas and mangoes, artificially contaminated with all species of Colletotrichum tested, during storage at room temperature. Furthermore, these coatings impacted positively on physicochemical parameters indicative of the postharvest quality of guava and mango, outstanding their effects on reduction of weight loss and ascorbic acid losses during storage. Sodium alginate coatings added from potentially probiotic fruit derived lactic acid bacteria strains can be considered innovative and effective strategies to reduce postharvest anthracnose development and prolong the storability of guava and mango.